RNAi-mediated silencing of the HD-Zip gene HD20 in Nicotiana attenuata affects benzyl acetone emission from corollas via ABA levels and the expression of metabolic genes - Ré, Delfina Adela (2012)
Background: The N. attenuata HD20 gene belongs to the homeodomain-leucine zipper (HD-Zip) type I family of transcription factors and it has been previously associated with the regulation of ABA accumulation in leaves and the emission of benzyl acetone (BA; 4-phenyl-2-butanone) from night flowers. In this study, N. attenuata plants stably reduced in the expression of HD20 (ir-hd20) were generated to investigate the mechanisms controlling the emission of BA from night flowers.Results: The expression of HD20 in corollas of ir-hd20 plants was reduced by 85 to 90% compared to wild-type plants (WT) without affecting flower morphology and development. Total BA emitted from flowers of ir-hd20 plants was reduced on average by 60%. This reduction occurred mainly at the late phase of BA emission and it was correlated with 2-fold higher levels of ABA in the corollas of ir-hd20 plants. When a 2-fold decline in ABA corolla levels of these plants was induced by salt stress, BA emissions recovered to WT levels. Supplying ABA to WT flowers either through the cuticle or by pedicle feeding reduced the total BA emissions by 25 to 50%; this reduction occurred primarily at the late phase of emission (similar to the reduction observed in corollas of ir-hd20 plants). Gene expression profiling of corollas collected at 12 pm (six hours before the start of BA emission) revealed that 274 genes changed expression levels significantly in ir-hd20 plants compared to WT. Among these genes, more than 35% were associated with metabolism and the most prominent group was associated with the metabolism of aromatic compounds and phenylpropanoid derivatives.Conclusions: The results indicated that regulation of ABA levels in corollas is associated with the late phase of BA emission in N. attenuata plants and that HD20 affects this latter process by mediating changes in both ABA levels and metabolic gene expression.